(untitled) (FLOVET - Boletim do Grupo de Pesquisa da Flora, Vegetação e Etnobotânica, 2025)
Invasive alien species are threats to ecosystems and the livelihoods of rural communities. This study analyzed the perception of farmers from Fazenda Bode, Parambu, Ceará, about the impacts of the invasive Cryptostegia madagascariensis. Semi-structured interviews were conducted with 20 farmers, complemented by field observations. All the interviewees reported knowing the species, which has been present in the region for over fifteen years. The main impacts pointed out were: a reduction in agricultural and fodder production (50%), the death of animals (15%), restricted access to water resources (75%) and the death of native species (70%). Most farmers do not adopt control methods, and the few that have been applied (cutting, burning, use of oil) have proved ineffective. It is concluded that the invasion by C. madagascariensis compromises the economy, animal health and local natural resources, highlighting the need for participatory management actions and specific public policies to mitigate its effects.